2009
DOI: 10.1152/ajpendo.00061.2009
|View full text |Cite
|
Sign up to set email alerts
|

The effects of amino acids on glucose metabolism of isolated rat skeletal muscle are independent of insulin and the mTOR/S6K pathway

Abstract: Two mechanisms have been proposed for the modulation of skeletal muscle glucose metabolism by amino acids. Whereas studies on humans and cultured cells suggested acute insulin desensitization via mammalian target of rapamycin (mTOR) and its downstream target p70 S6 kinase (S6K), investigations using native specimens of rat muscle hinted at impairment of glucose oxidation by competition for mitochondrial oxidation. To better understand these seemingly contradictory findings, we explored the effects of high conc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 28 publications
(25 reference statements)
0
4
0
Order By: Relevance
“…Increased level and activity of this target have been found to be induced by insulin. 99,100 Interestingly, this signaling has been demonstrated in 60% of HCC cases, which promoted cell cycle progression, proliferation, growth, and angiogenesis. [101][102][103][104][105] Regarding the relation between let-7a, miR-34a, and miR-199a/b and MTOR as a direct target in insulin signaling, it has been shown that insulin stimulation inhibits the expression of miR-199a-5p.…”
Section: Insulin Signalingmentioning
confidence: 99%
“…Increased level and activity of this target have been found to be induced by insulin. 99,100 Interestingly, this signaling has been demonstrated in 60% of HCC cases, which promoted cell cycle progression, proliferation, growth, and angiogenesis. [101][102][103][104][105] Regarding the relation between let-7a, miR-34a, and miR-199a/b and MTOR as a direct target in insulin signaling, it has been shown that insulin stimulation inhibits the expression of miR-199a-5p.…”
Section: Insulin Signalingmentioning
confidence: 99%
“…Fuel metabolism of native skeletal muscle was examined along procedures established at our laboratory (2,3,26). Food, but not water, was withdrawn from 6-to 8-wk-old rats for 3-4 h, before they were briefly anesthetized and killed by cervical dislocation for the preparation of two longitudinal strips of soleus muscle per leg.…”
Section: Ratsmentioning
confidence: 99%
“…Analytical methods have been outlined in more detail elsewhere (26). In short, rates of CO2 production from glucose or palmitate (referred to as glucose and palmitate oxidation) were measured in separate runs as calculated from the conversion of [ 14 C]glucose or of [ 14 C]palmitate into 14 CO2, which was trapped with a solution containing methanol and phenethylamine (1:1).…”
Section: Ratsmentioning
confidence: 99%
“…These results are consistent with our observation that mTOR was inhibited by miR-99a in hepatocellular carcinoma cells (HCC). It has been demonstrated that insulin can regulate glucose metabolism by activating mTOR pathway [19], [20]. The liver is known to be important in regulating glucose metabolism in response to growth factors and insulin treatment [21], [22].…”
Section: Introductionmentioning
confidence: 99%